2002
DOI: 10.1002/ajh.10210
|View full text |Cite
|
Sign up to set email alerts
|

In vitro production of anti‐RBC antibodies and cytokines in chronic lymphocytic leukemia

Abstract: B-chronic lymphocytic leukemia (B-CLL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 36 publications
0
13
0
2
Order By: Relevance
“…Mitogen-stimulated DAT (MS-DAT) is another technique that can be used to diagnose the presence of latent anti-red cell antibodies. Barcellini et al (2002) reported 28AE9% prevalence of anti-red cell antibodies by using MS-DAT while conventional DAT was positive in only 4AE3% patients. Use of rituximab in FCR may be the factor that contributes to the masking of DAT positivity.…”
Section: Discussionmentioning
confidence: 97%
“…Mitogen-stimulated DAT (MS-DAT) is another technique that can be used to diagnose the presence of latent anti-red cell antibodies. Barcellini et al (2002) reported 28AE9% prevalence of anti-red cell antibodies by using MS-DAT while conventional DAT was positive in only 4AE3% patients. Use of rituximab in FCR may be the factor that contributes to the masking of DAT positivity.…”
Section: Discussionmentioning
confidence: 97%
“…The quantification of anti-RBC-bound IgG in mitogenstimulated cultures was evaluated with MS-DAT, as previously described [9,11]. Fresh heparinized blood samples were diluted 1:6 with RPMI 1640 medium (Gibco) and either stimulated or not stimulated with mitogens (2 lg/ml phytohemagglutinin (PHA), 20 ng/ml phorbol miristate acetate (PMA), or 1% pokeweed (PWM, Sigma, St. Louis, MO, USA) in 24-well plates for 48 h. RBCs were washed four times with phosphate-buffered saline (PBS), centrifuged at 1,000 rpm for 10 min, resuspended in PBS at 10% concentration, and processed for the quantitation of antiautologous RBC-bound IgG.…”
Section: Anti-rbc-bound Igg Quantification By Ms-datmentioning
confidence: 99%
“…More recently, mitogen-stimulated (MS)-DAT has been proposed as a functional and quantitative method for the detection of anti-RBC antibodies in mitogen-stimulated whole-blood cultures; the test could identify cytokine modulation of anti-RBC antibody production in AIHA [9], and facilitated the diagnosis of some DAT-negative AIHA cases [10]. Moreover, MS-DAT was found to be positive in a fraction of B-chronic lymphocytic leukemia (B-CLL) patients without an overt diagnosis of AIHA, suggesting that in vitro mitogen stimulation could be used to identify latent anti-RBC autoimmunity in B-CLL [11].…”
Section: Introductionmentioning
confidence: 99%
“…Análise multivariada revelou que a IL-4 foi significantemente mais elevada, e o IFN-γ foi significantemente mais baixo em pacientes com LLC e TAD positivo. 15 A participação de genes V H na fisiopatologia da AHAI secundária à LLC é questionável. Em estudo com apenas 12 indivíduos com AHAI associada à LLC foi verificada a presença de V 1-69 em cinco e V 3-33 em quatro pacientes, mas em nenhum de 12 indivíduos do grupo controle.…”
Section: Mecanismos Biológicos Da Auto-imunidade Na Llcunclassified